Analisis Jaringan Komunikasi pada Agribisnis Sayuran Organik di Kabupaten Bandung Barat - Budi Kusumo, Rani Andriani; Anne Charina (Jurnal Penyuluhan, 2021)
Organic vegetable business opportunities are quite potential with the spread of a healthy lifestyle through the consumption of organic products. The problems faced by organic vegetable farmers include the use of technology and information that is not optimal. This study aims to analyze the communication network on organic vegetable agribusiness in West Bandung Regency; and analyzing the relationship between the communication network and the capacity of organic vegetable farmers in West Bandung Regency. This research used quantitative methods with survey techniques. The total respondents who were analyzed were 105 organic vegetable farmers in Lembang, Cisarua and Parongpong Districts who were selected using systematic random sampling technique. The results of the sociogram analysis showed that the communication network in organic vegetable agribusiness has a personal structure that spreads centrally (interlocking personal network). This diffuse and concentrated pattern in each click occurred because the areas where farmers lived were far from one another and the ability of farmers to access information sources varied. Farmers who have high capacity in managing organic vegetable farming are generally active in seeking information, and are able to market their products directly to the modern retail market, whereas farmers with moderate capacity tend to establish contacts and relationships that are limited to their community.